Forgetting the new locations of one’s keys: spatial-memory interference in Korsakoff’s amnesia - Postma, Albert (Exp Brain Res, 2018)
The present study focused on interference in a group of patients with amnesia due to Korsakoff’s syndrome (KS) within the domain of spatial memory. An object–location memory task was used in which participants first learned an array of objects on a computer screen, followed by a reconstruction of the object positions. Next a trial was given in which the same objects were presented only now in different locations. Participants had to place the objects a second time but at the new locations. This was repeated for seven pairs of baseline/interference trials. Both Korsakoff patients and matched controls did worse on the interference trials than on the baseline trials, indicating that it is difficult to relearn new spatial locations for objects that previously were remembered in other locations. When computing relative interference effects (that is the percentage change from baseline in the interference trials), Korsakoff patients were less affected than controls. It is discussed in how far interference depends on the strength of the original memories, which are markedly lower in KS patients.